Scholarly manuscript assessment: Scientific journal editor desk evaluation - Erikson Saragih; Kundharu Saddhono; Nurenzia Yannuar; Desri Maria Sumbayak (Malaysian Journal of Library and Information Science, 2024)
Rejection of submitted articles during the editorial review process can be discouraging for authors. This study investigates the factors affecting manuscript acceptance and rejection by journal editors and proposes targeted training to enhance acceptance rates at the editorial review stage. Data were collected through online questionnaires from 42 international journal editors, interviews with five editors, and focus group discussions with graduate students. The findings reveal that editors consider six key criteria when deciding whether to accept manuscripts for peer review: originality, uniqueness, scope, appropriateness, relevance, and significance. Commonly rejected sections include the abstract, methods, and results. Insights from editor interviews and focus groups with early-career researchers shed light on the reasons for manuscript rejection and highlight specific sections with higher rejection rates. The study recommends that new researchers undertake courses in scientific writing to better understand editors’ evaluation criteria and improve their chances of acceptance.